Mandatory CSR reporting—literature review and future developments in Germany - Gulenko, Maryna (NachhaltigkeitsManagementForum | Sustainability Management Forum)

Failure behavior of short glass fiber reinforced polyamide under superimposed mechanical-enviromental fatigue - Brandler , Patrick R.

Analyse und Modellierung des Reckverfahrens von mono- und biaxial verstreckten Polypropylenfolien - Reinders , Frauke

Charakterisierung des Bruchverhaltens von Polypropylen-Celluloseregeneratfaser-Verbunden - Zarges, Jan-Christoph

Inverse thermische Spritzgießwerkzeugauslegung auf Basis des lokalen Kühlbedarfs - Nikoleizig , Philipp Alexander

Effects of breastfeeding on health outcomes in childhood: beyond dose-response relations - Buyken, Anette; Karaolis-Danckert, Nadina; Günther, Anke; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Habitual Flavonoid Intake from Fruit and Vegetables during Adolescence and Serum Lipid Levels in Early Adulthood: A Prospective Analysis - Penczynski, Katharina; Remer, Thomas; Herder, Christian; Kalhoff, Hermann; Rienks, Johanna; Markgraf, Daniel; Roden, Michael; Buyken, Anette (Nutrients)

In adolescence a higher ‘eveningness in energy intake’ is associated with higher total daily energy intake - Diederichs, Tanja; Perrar, Ines; Roßbach, Sarah; Alexy, Ute; Buyken, Anette (Appetite)

Positive Effects of Practical Nutrition Lessons in a Primary SchoolSetting with a High Proportion of Migrant School Children - Weber, Katharina S.; Eitner, Jessica; Dauben, Laura; Spörkel, Olaf; Strassburger, Klaus; Sommer, Jörn; Kaiser, Barbara; Buyken, Anette; Kronsbein, Peter; Müssig, Karsten (Experimental and Clinical Endocrinology & Diabetes)
Abstract Background Children with migration background are at increased risk for overweight, partly due to less favorable dietary habits compared to their German counterparts. We examined the effects of practical nutrition lessons among children with a high proportion of migration background in a primary school setting. Methods Ten 3rd and 4th grade classes (n=166 children, 73% with migration background) received the intervention and nine school classes (n=139 children, 76% with migration background) served as control. Before, shortly after (only among the intervention group) and three months after the three-day practical nutrition lessons, the nutrition-related skills, behavior, attitudes, and knowledge of the children were assessed using a questionnaire. Changes between baseline and 1st follow-up among children of the intervention group were calculated using linear mixed models. Differences between the two groups for changes between baseline and 2nd follow-up were tested using linear regression analyses. Models were adjusted for potential confounders. Results Shortly after the practical nutrition lessons, the children of the intervention group had improved their knowledge (β=1.7; 95% CI: 1.0; 2.4, P<0.001) and skills (β=1.8; 95% CI: 1.4; 2.2, P<0.001). These changes were sustainable and larger in the intervention compared to the control group (knowledge: β=1.6; 95% CI: 0.7; 2.5, P<0.001; skills: β=1.3; 95% CI: 0.7; 1.9, P<0.001). Changes in nutrition-related behavior and attitudes did not differ between the groups. Conclusions Providing practical nutrition lessons in a primary school setting with a high proportion of children with immigrational background improved the children’s nutrition-related knowledge and skills.

Time and age trends in morning and evening protein intakes of German children and adolescents - Roßbach, Sarah; Diederichs, Tanja; Herder, Christian; Buyken, Anette; Alexy, Ute (Journal of Nutritional Science)
Abstract The present study describes time and age trends in morning and evening protein intakes and sources among German children and adolescents from 1985 to 2014. A total of 9757 three-day weighed dietary records of 1246 3- to 18-year-old participants of the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were analysed using polynomial mixed-effects regression models. Morning protein intake increased over the study period by approximately 1 % of morning energy intake (linear trend P < 0·0001), with the youngest and the oldest children having the highest protein intake (linear, quadratic trend P < 0·0001). Evening protein intake increased over time by approximately 2 % of evening energy intake in girls (linear trend P < 0·0001) and 1 % of evening energy intake in boys (quadratic trend P = 0·0313), with decreasing intake with age (girls: linear trend P < 0·0001; boys: linear trend P = 0·0963). Time trends were largely due to increases in protein from ‘starchy foods’. In conclusion, morning and evening protein intakes increased modestly between 1985 and 2014; these increases were, however, not accompanied by increases in traditional protein sources (i.e. meat or dairy products).

Schule und Bildungsadministration im Dialog – Eine qualitative Untersuchung über die Kooperation zwischen der schulischen Praxis und der Qualitäts- und Unterstützungsagentur NRW - Drossel, Kerstin (Does ‚What works‘ work? – Bildungsforschung, Bildungsadministration und Bildungspolitik im Dialog)

Die Relevanz schulischer IT-Ausstattungskonzepte für die Implementierung neuer Technologien in Schulen - Eickelmann, Birgit; Drossel, Kerstin; Gerick, Julia (Medien und Erziehung)

Determinanten der unterrichtlichen Computernutzungshäufigkeit und der medienbezogenen Kooperation. Eine Analyse auf Grundlage des Länderindikators 'Schule digital' - Drossel, Kerstin; Eickelmann, Birgit; Lorenz, Ramona (Unterrichtswissenschaft)

Eine geschlechtsspezifische Analyse zum schulischen Erwerb computerbezogener Kompetenzen in Tablet-Klassen am Gymnasium - Massek, Corinna; Drossel, Kerstin; Eickelmann, Birgit (MedienImpulse)
Aufgrund gesellschaftlicher Veränderungen und der steigenden Relevanz eines kompetenten, selbstbestimmten und reflektierten Umgangs mit digitalen Medien, ergeben sich auch für Schulen neue Herausforderungen, den Erwerb entsprechender Kompetenzen zu unterstützen. Studien deuten bzgl. des Kompetenzerwerbs auf Disparitäten zwischen Mädchen und Jungen hin – Mädchen schneiden in computer- und informationsbezogenen Kompetenzen besser ab und geben zu höheren Anteilen an, diese Kompetenzen schulisch erworben zu haben. Hinsichtlich der Vermittlung dieser Kompetenzen deuten aktuelle Entwicklungen darauf hin, dass Schulen vermehrt auf 1:1-Ausstattung mit digitalen Medien setzen, da vor allem schülereigenen mobilen Endgeräten vielseitige Potenziale zugeschrieben werden. Der Beitrag fokussiert daher auf Grundlage eines Tablets-Projekts die Frage, ob die Einführung schülereigener Tablets den schulischen Kompetenzerwerb für Mädchen und Jungen tatsächlich unterstützt. Im Ergebnis zeigt sich, dass die Einführung von Tablets nicht automatisch dazu führt, dass Mädchen und Jungen gleichermaßen einen schulischen Kompetenzerwerb wahrnehmen.

Digitale Medien in TIMSS 2015 und IGLU 2016. Ergebnisse zur Nutzung und zum Stellenwert von Lehrerfortbildungen für Grundschulen in Deutschland im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin (SchulVerwaltung NRW)

Die Rolle der Lehrerprofessionalisierung für die Implementierung neuer Technologien in den Unterricht – Eine Latent-Class-Analyse zur Identifikation von Lehrertypen - Drossel, Kerstin; Eickelmann, Birgit (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Mangelnde medienpädagogische Kompetenzen stellen für Lehrpersonen einen Hemmfaktor dar, digitale Medien in unterrichtliche Lehr-Lernprozesse zu integrieren. Fortbildungen sowie Lehrerkooperationen bieten in diesem Kontext Ansatzpunkte für Lehrerprofessionalisierungsmassnahmen (Drossel et al. 2016; Herzig 2007; Weiß und Bader 2010). Im internationalen Vergleich zeigt sich jedoch, dass Lehrpersonen in Deutschland selten an Professionalisierungsmassnahmen teilnehmen (Gerick et al. 2014).
Bisherige Befunde berücksichtigen allerdings nicht, dass das medienpädagogische Professionalisierungsverhalten stark variiert (Lorenz et al. 2016), was sich vermutlich in unterschiedlicher Weise auf die unterrichtliche Nutzung digitaler Medien auswirkt. Dieses Forschungsanliegen greift dieser Beitrag auf Grundlage von Sekundäranalysen der Lehrerdaten (N=1.377) der IEA-Studie ICILS 2013 (Bos, Eickelmann et al. 2014) auf und untersucht entlang des theoretischen Rahmenmodells der Studie, ob sich in Deutschland hinsichtlich der Professionalisierung Lehrertypen identifizieren lassen und welcher Zusammenhang zur unterrichtlichen Nutzung digitaler Medien sowie zu weiteren Prädiktoren der Mediennutzung besteht.
Anhand einer Latent Class Analyse können zwei Gruppen identifiziert werden: die zurückhaltenden (85%) sowie die engagierten Professionalisierer (15%). Die Professionalisierung beider Gruppen erfolgt eher im internen Bereich, wobei sie bei den engagierten Professionalisierern höher ausfällt. Engagierte Professionalisierer nutzen zudem häufiger digitale Medien im Unterricht, schätzen ihre computerbezogenen Fähigkeiten höher ein und geben in einem höheren Masse an, die computerbezogenen Kompetenzen der Schülerschaft zu fördern.

Distributed Algorithms for Overlay Networks and Programmable Matter - Gmyr, Robert

Self-Stabilizing Supervised Publish-Subscribe Systems - Feldmann, Michael; Kolb, Christina; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
In this paper we present two major results: First, we introduce the first self-stabilizing version of a supervised overlay network (as introduced in~\cite{DBLP:conf/ispan/KothapalliS05}) by presenting a self-stabilizing supervised skip ring. Secondly, we show how to use the self-stabilizing supervised skip ring to construct an efficient self-stabilizing publish-subscribe system. That is, in addition to stabilizing the overlay network, every subscriber of a topic will eventually know all of the publications that have been issued so far for that topic. The communication work needed to processes a subscribe or unsubscribe operation is just a constant in a legitimate state, and the communication work of checking whether the system is still in a legitimate state is just a constant on expectation for the supervisor as well as any process in the system.
Keywords: Topological Self-stabilization; Supervised Overlay; Publish-Subscribe System

Skueue: A Scalable and Sequentially Consistent Distributed Queue - Feldmann, Michael; Scheideler, Christian; Setzer, Alexander (Proceedings of the 32nd IEEE International Parallel & Distributed Processing Symposium (IPDPS))
We propose a distributed protocol for a queue, called Skueue, which spreads its data fairly onto multiple processes, avoiding bottlenecks in high throughput scenarios. Skueuecan be used in highly dynamic environments, through the addition of join and leave requests to the standard queue operations enqueue and dequeue. Furthermore Skueue satisfies sequential consistency in the asynchronous message passing model. Scalability is achieved by aggregating multiple requests to a batch, which can then be processed in a distributed fashion without hurting the queue semantics. Operations in Skueue need a logarithmic number of rounds w.h.p. until they are processed, even under a high rate of incoming requests.

Making the Case for Proof-carrying Approximate Circuits - Witschen, Linus Matthias; Wiersema, Tobias; Platzner, Marco (4th Workshop On Approximate Computing (WAPCO 2018))